Overcoming communication apprehension with emotional intelligence skills - Thomas, Mary; Noordin, Nooreen; Francis, Peter (Centre of Excellence for Scientific & Research Journalism, 2016)
Good communication skill in the English language is a necessity for graduates in a second language learning environment to ensure that they can secure employment upon graduation. To be successful communicators, learners must be able to deal with their apprehension appropriately which can be difficult especially for learners with low self-esteem and those who fear that they are incompetent in the English language. This study explores the potential of emotional intelligence as a means to overcome communication apprehension among tertiary learners. The instruments used to measure these two variables are the Emotional Skills Profile (ESAP) by Nelson and Low (2011) and the Personal Report of Communication Apprehension (PRCA24) by McCroskey (1982). The results indicate a significant negative association between emotional intelligence and communication apprehension. The regression analysis shows that intrapersonal, self-management and personal leadership are important predictors in determining communication apprehension levels. Hence, it is vital for language educators to incorporate emotional intelligence within the language curriculum to enhance learners’ confidence in using the second language.